A regression discontinuity analysis of the social distancing recommendations for older adults in Sweden during COVID-19. (13th August 2022) - Bonander, Carl; Stranges, Debora; Gustavsson, Johanna; Almgren, Matilda; Inghammar, Malin; Moghaddassi, Mahnaz; Nilsson, Anton; Capdevila Pujol, Joan; Steves, Claire; Franks, Paul W; Gomez, Maria F; Fall, Tove; et al.
Abstract: Background: This article investigates the impact of a non-mandatory and age-specific social distancing recommendation on isolation behaviours and disease outcomes in Sweden during the first wave of the coronavirus disease 2019 (COVID-19) pandemic (March to July 2020). The policy stated that people aged 70 years or older should avoid crowded places and contact with people outside the household. Methods: We used a regression discontinuity design—in combination with self-reported isolation data from COVID Symptom Study Sweden ( n  = 96 053; age range: 39–79 years) and national register data (age range: 39–100+ years) on severe COVID-19 disease (hospitalization or death, n  = 21 804) and confirmed cases ( n  = 48 984)—to estimate the effects of the policy. Results: Our primary analyses showed a sharp drop in the weekly number of visits to crowded places (−13%) and severe COVID-19 cases (−16%) at the 70-year threshold. These results imply that the age-specific recommendations prevented approximately 1800–2700 severe COVID-19 cases, depending on model specification. Conclusions: It seems that the non-mandatory, age-specific recommendations helped control COVID-19 disease during the first wave of the pandemic in Sweden, as opposed to not implementing a social distancing policy aimed at older adults. Our study provides empirical data on how populations may react to non-mandatory, age-specific social distancing policies in the face of a novel virus.